Stakeholders e as smart cities - Costa, Jefferson Cirne da (2021)
Urban environments are increasingly populated, complex and challenging. Bringing intelligence to the management model of these cities has been presented as a viable alternative to improving the quality of life of the population that resides in them. However, there is no relevant and sufficient study that seeks to identify these stakeholders within the scope of smart cities, nor assess their importance in this context, and even investigate whether the city's performance is related to the perception of these non-governmental stakeholders. And this is the central proposal of this work, consisting of multiple, distinct and interdependent studies, being a systematic literature review and a quantitative method through varied regressions. The perception of public managers in relation to the salience of other stakeholders does not impact the municipality's performance, even though the literature has recognized and typified such stakeholders, with civil society being the most recognized stakeholder in the revised texts. The impact on the performance of cities is only observed in relation to geographic and economic aspects. It is desirable to develop a scale to measure the attributes and salience of stakeholders, in addition to investigating more characteristics of public managers. Another proposal for future studies would be to investigate the reason for the educational segment to be more salient in the eyes of public managers than the authors of scientific articles.